Gene action for seed yield and yield components in sesame (Sesamum indicum) - KAMALA, T (The Indian Journal of Agricultural Sciences, 2013)
In a 6 x 6 full diallel experiment conducted during 1996 - ’97 with sesame (Sesamum indicum L.) of numerical and graphical analyses days to maturity was found highly heritable with additive effects, whereas plant height, branches, capsules/plant. seeds/capsule, 1000 seed weight and seed yield/plant were moderate to low heritable with non-additive effects in the form of dominance. Impact of season on the genetic expression was non-significant and the 6 parents ’TMV 5’ mutant, ’Vinayak mutant, ’S1266’, ’RJS108’, ’SI3260’ and ’Madhavi’ showed genetic diversity for all the 7 characters. The predominance of both additive and non-additive gene influence showed the high genetic potential ofthe 6 parents for exploiting desirable economic heterosis.